Memerkarakan Identitas Nasional: Representasi Identitas Kultural dalam Sinema Generasi Baru Indonesia dan Malaysia - Irawanto, Budi (Jurnal Ilmu Sosial dan Ilmu Politik, 2008)
Cinema has been long seen as a trans-cultural phenomenon due to its cross-cultural ability. Cinema posits itself to entertain and to educate people from various backgrounds by using its "universal language" âembracing visual and aesthetic aspects. At the same time, cinema has potentials to bring the discourse of identity. The issue of identity will strongly emerge in cinemas, particularly when a country faces a crisis of identity. Many cases show that cinema plays a significant role in contesting the idea of national identity. Moreover, this article aims at highlighting the notion of identity attached in cinema production. By using comparative perspectives between Indonesia and Malaysia, this paper shows how creative spaces are constructed by new generation of Indonesian and Malaysian film makers. Creative spaces which are initiated by cineaste are intended to open the path for critical ideas on national identity. Instead of a fixed state, national identity is defined by young generation of filmmakers more as a contested idea.